Dietary Patterns High in Red Meat, Potato, Gravy, and Butter Are Associated with Poor Cognitive Functioning but Not with Rate of Cognitive Decline in Very Old Adults. Issue 2 (6th January 2016) - Granic, Antoneta; Davies, Karen; Adamson, Ashley; Kirkwood, Thomas; Hill, Tom R; Siervo, Mario; Mathers, John C; Jagger, Carol
Abstract: Background: Healthy dietary patterns (DPs) have been linked to better cognition and reduced risk of dementia in older adults, but their role in cognitive functioning and decline in the very old (aged ≥85 y) is unknown. Objective: We investigated the association between previously established DPs from the Newcastle 85+ Study and global and attention-specific cognition over 5 y. Methods: We followed up with 302 men and 489 women (1921 birth cohort from Northeast United Kingdom) for change in global cognition [measured by the Standardized Mini-Mental State Examination (SMMSE)] over 5 y and attention (assessed by the cognitive drug research attention battery) over 3 y. We used 2-step clustering to derive DPs and mixed models to determine the relation between DPs and cognition in the presence of the dementia susceptibility gene. Results: Previously, we characterized 3 DPs that differed in intake of red meat, potato, gravy, and butter and varied with key health measures. When compared with participants in DP1 (high red meat) and DP3 (high butter), participants in DP2 (low meat) had higher SMMSE scores at baseline ( P < 0.001) and follow-ups, and better initial attention ( P < 0.05). Membership in DP1 and DP3 was associated with overall worse SMMSE scores (β = 0.09, P = 0.01 and β = 0.08, P = 0.02, respectively) than membership in DP2 after adjustment for sociodemographic factors, lifestyle, multimorbidity, and body mass index (BMI). Additional adjustment for apolipoprotein ( apoE ) ε4 genotype attenuated the association to nonsignificant in women but not in men in DP1 (β = 0.13, P = 0.02). Participants in DP1 and DP3 also had overall worse concentration (β = 0.04, P = 0.002 and β = 0.028, P = 0.03, respectively) and focused attention (β = 0.02, P = 0.01 and β = 0.02, P = 0.03, respectively), irrespective of apoE ε4 genotype, but similar rate of decline in all cognitive measures over time. Conclusion: DPs high in red meat, potato, gravy (DP1), or butter (DP3) were associated with poor cognition but not with the rate of cognitive decline in very old adults.